PSIKOLOGI DAN DAKWAH : AKTIVITAS DAKWAH TERHADAP ODGJ DALAM KONTEN YOUTUBE â€œPRATIWI NOVIYANTHIâ€ - Rizal Effendi Putra; Muhammad Irham; Ressa Azhara Joneva (LPPM STISIP Persada Bunda, 2023)
Da'wah becomes an Islamic communication and has an effort to influence other people so that they behave and behave as preached. Directly invites to the way of Allah amar ma'ruf nahi munkar to achieve human happiness in the world and the hereafter. When preaching the da'i must be more familiar with the psychological condition of the object first. Based on psychological elements, the da'wah process will run according to the needs expected by humans as individuals and social beings. This study aims to find out what messages and roles are found in the youtube content